1987
DOI: 10.1523/jneurosci.07-03-00682.1987
|View full text |Cite
|
Sign up to set email alerts
|

Schwann cell proliferation and migration during paranodal demyelination

Abstract: This study examined Schwann cell behavior during paranodal demyelination induced by beta,beta'-iminodipropionitrile (IDPN). The stimuli for Schwann cell proliferation, extensively studied in vitro, are less well understood in vivo. Most in vivo systems previously used to examine Schwann cell proliferation in disease are dominated by loss of internodal myelin sheaths. As used in this study, IDPN administration produces neurofilamentous axonal swellings and paranodal demyelination, without segmental demyelinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(46 citation statements)
references
References 22 publications
1
45
0
Order By: Relevance
“…Systemic administration of IDPN results in impaired neurofilament transport and the formation of large neurofilamentous axonal swellings beginning just beyond the initial segment and occupying the first several internodes (Griffin et al, 1987) (see Fig. 4).…”
Section: Schwann Cell Responses In Demyelinationmentioning
confidence: 99%
“…Systemic administration of IDPN results in impaired neurofilament transport and the formation of large neurofilamentous axonal swellings beginning just beyond the initial segment and occupying the first several internodes (Griffin et al, 1987) (see Fig. 4).…”
Section: Schwann Cell Responses In Demyelinationmentioning
confidence: 99%
“…Previous studies of nerves undergoing demyelination reached similar conclusions. In the models of lysophosphatidyl choline application (Griffin et al, 1990) and 3,3-iminodipropionitrile (Griffin et al, 1987) administration, internodal and paranodal demyelination, respectively, were associated with entry of RSCs into the cell cycle. In those models, it was difficult to exclude a degree of injury to the axons of unmyelinated fibers.…”
Section: Discussionmentioning
confidence: 99%
“…Such an observation would suggest that diffusible mitogens, capable of signaling Schwann cells that neighbor degenerating axons, might be important. Previous studies of demyelinating nerve injury showed division of Schwann cells associated with uninjured Remak bundles, but a direct effect on Remak Schwann cells could not be excluded (Griffin et al, 1987(Griffin et al, , 1990. In this study, we used ventral rhizotomy as a model of selective nerve injury in the rat.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations